Understanding of the Policy on Fostering Street Vendors in Surabaya: A Review of Surabaya City Regulation No. 17 Year 2003 - Basa Alim Tualeka; Abdul Rohim Tualeka; Juliana Jalaludin; Salsabila Novianti (Poltekkes Kemenkes Surabaya, 2024)
This research aims to understand the policy of fostering street vendors in Surabaya through a study of Surabaya City Regional Regulation No. 17 Year 2003. It was conducted using qualitative research on street vendors and the Surabaya City Government, opening up the possibility of various information materials from all sources. The results show that a) street vendors fostered by the Surabaya City Government have a unique character; on the one hand, they receive coaching assistance from the government, but on the other hand, they sometimes oppose government policies that touch their interests. In general, the fostered street vendors have peace in doing business and become partners of the Surabaya City Government; b) street vendors fostered by the Surabaya City Government have experienced increased welfare financially and socially. Surabaya City Government has made various efforts to foster street vendors to create a clean, orderly, beautiful, and safe Surabaya city.